Situational Cases as Means of Forming the Methodological Culture of Future Social Pedagogue (Journal of Educational Sciences, 2025)
The need for qualified teachers has arisen as a result of changes in society and the economy, technological advancements, and the escalation of social and political instability. A social pedagogue’s professional competency is defined by the unity of his theoretical and practical readiness to carry out social and pedagogical activities, as well as by his professionalism, professional knowledge, and abilities. The high standards of society dictate the future social pedagogue’s competency and versatility in his work. A social pedagogue’s professional competence is a combination of mental attributes that enable one to behave properly and autonomously in social and educational contexts. A skilled professional is prepared to autonomously decide on social and educational initiatives, carry them out, and take responsibility for the outcomes. In order to ensure that aspiring social pedagogues are fully immersed in the field, the article presents an analysis of the impact of situational cases on the level of their methodological culture. The study was conducted based on the author’s diagnostic instruments accounting for the specifics of each phase of the investigation. Furthermore, an examination of a particular professional scenario served as the foundation for each diagnostic instrument. A person-oriented empirical approach, which is typically regarded as a priority for the development of professional practice and teaching techniques of social pedagogy, serves as the scientific and methodological foundation for the research presented in this article. The research’s foundation included the application of descriptive statistical techniques correlation analysis, and Student’s T-test. Data processing was carried out using the statistical package SPSS.22. In addition to providing opportunities for new study, the data can be utilized for personnel selection, advanced training and retraining programmers for social pedagogues, as well as for professional self-determination of specialists at this level.Key words: social pedagogue, methodological culture, school education, immersion in the profession, professional situation.